Non-Mendelian inheritance patterns and extreme deviation rates of CGG repeats in autism - Annear, Dale J.; Vandeweyer, Geert; Sanchis-Juan, Alba; Raymond, F. Lucy; Kooy, R. Frank

(untitled) (Genome Research, 2022)
As expansions of CGG short tandem repeats (STRs) are established as the genetic etiology of many neurodevelopmental disorders, we aimed to elucidate the inheritance patterns and role of CGG STRs in autism-spectrum disorder (ASD). By genotyping 6063 CGG STR loci in a large cohort of trios and quads with an ASD-affected proband, we determined an unprecedented rate of CGG repeat length deviation across a single generation. Although the concept of repeat length being linked to deviation rate was solidified, we show how shorter STRs display greater degrees of size variation. We observed that CGG STRs did not segregate by Mendelian principles but with a bias against longer repeats, which appeared to magnify as repeat length increased. Through logistic regression, we identified 19 genes that displayed significantly higher rates and degrees of CGG STR expansion within the ASD-affected probands (P < 1 × 10−5). This study not only highlights novel repeat expansions that may play a role in ASD but also reinforces the hypothesis that CGG STRs are specifically linked to human cognition.